1982
DOI: 10.1126/science.6801766
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae Infection: Role of a Surface Protein in the Attachment Organelle

Abstract: Attachment of Mycoplasma pneumoniae to host cell by means of a specialized terminus initiates infection. Monoclonal antibodies to a surface protein (Pl) inhibit this process, and react with a region of the tip covered with peplomer-like particles. Since antibodies against the Pl protein are generated by natural and experimental infection and by immunization, the substance may be an important determinant of protective immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
0
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(144 citation statements)
references
References 10 publications
4
138
0
2
Order By: Relevance
“…To ensure optimal protease concentrations, antiserum against P1 protein and EF-G served as controls. P1 is the major adhesin of M. pneumoniae (3,25), and EF-G is a cytosolic protein. The control experiments showed that the proteinase K concentration used for the cleavage experiment is critical, since the range of protease concentration necessary for complete cleavage of P1 without affecting EF-G was very narrow (0.8 to 1.2 U/ml).…”
Section: Detection Of P65 In Triton X-100-insoluble Subfractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure optimal protease concentrations, antiserum against P1 protein and EF-G served as controls. P1 is the major adhesin of M. pneumoniae (3,25), and EF-G is a cytosolic protein. The control experiments showed that the proteinase K concentration used for the cleavage experiment is critical, since the range of protease concentration necessary for complete cleavage of P1 without affecting EF-G was very narrow (0.8 to 1.2 U/ml).…”
Section: Detection Of P65 In Triton X-100-insoluble Subfractionsmentioning
confidence: 99%
“…A critical step in bacterial colonization of the host cells is the specific adhesion to host cell receptors, mediated by bacterial adhesins. In M. pneumoniae, the P1 adhesin (3,17,25,26) and the adhesin-related 30-kDa protein (4, 10) have been identified. Both proteins are located mainly in a tip structure that functions as the attachment organelle of the bacterium.…”
mentioning
confidence: 99%
“…The fibrillar element was well stained with ruthenium red, which specifically stains mucopolysaccharides. The second structure, observed by negative staining of M. pneumoniae, is a peplomer-like structure, called "nap" (1,10). The localization of nap is also restricted to the extracellular surface of the attachment organelle, similar to the distribution of spikes on the head-like protrusion of M. mobile.…”
mentioning
confidence: 98%
“…The protein with the higher molecular mass, estimated at 170-190 kDa, was named P1 (Hu et al, 1977). Subsequent studies established that protein PI is the major adhesin of M. pneumoniae (Hu et al, 1982;Baseman et al, 1982;Feldner et al, 1982). M .…”
Section: The P1 Operon Genes and Proteinsmentioning
confidence: 99%